Interaksi Liburan Murah Ala Komunitas Cikarang Baru Di Botanical Garden Eco Park Jababeka - Engkom Komariah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Holidays are an important aspect of life in modern society. In a social context, holidays also serve as a means to strengthen relationships between family members and friends. Community plays a very important role in creating an affordable holiday experience. Botanical Garden Eco Park Jababeka is one of the locations that is increasingly popular among the Cikarang Baru community as an affordable holiday spot. This research uses a descriptive qualitative approach to understand the phenomenon of affordable holiday interactions among the Cikarang Baru community. This method allows researchers to explore in-depth information about the experiences and perceptions of community members during holiday activities. Members of the Cikarang Baru community choose low-cost holidays as an alternative to save money in the midst of uncertain economic conditions. Based on interviews with community members, many of them revealed that budget constraints were the main factor in determining holiday destinations. Social interactions that occur during holiday activities at Botanical Garden Eco Park Jababeka are very diverse, consisting of individuals with different backgrounds. The Cikarang Baru community has several motivations that underlie the organisation of low-cost holidays at Botanical Garden Eco Park Jababeka. the most striking characteristics are collaboration and mutual cooperation between members. The positive impact of this low-cost holiday activity is very significant, both for individuals and the community as a whole.